Ungraduate students view on the presence of clown-doctors at the University Hospital - Gabriela Maia Mota; Daniel Magalhães Coutinho Mota; Márcia Maria Tavares Machado; Rebecca Holanda Arrais; Carla Pires Vieira de Oliveira; Melissa do Santos Salgado; Miliany Michelly Barreto de Souza; Lorena de Holanda William (Universidade de Fortaleza, 2012)
Objectives: To understand how students perceive the humanization of health, as well as the contributions of Project Y "clown doctors" in academic and hospital routine, identifying the relevance of this group through the construction of new paradigms. Methods: The study involved qualitative dimension, with the participation of medical students / interns in psychology and pediatric ward from a university hospital in Fortaleza - CE, Brazil. From March to July 2009, ten interviews were performed, recorded and fully transcribed and analyzed by interpretative network, comprising the categories: knowing the Project Y: different forms cognizable; role of Project Y in the hospital environment: the perception of this strategy in view of the spectators; humanization in health: the look of the future professional. The interpretive framework includes concepts related to health promotion activities, based in the humanization of care performed by graduate students in training. Results: Studentshave known Project Y from the observation of the activities performed in the infirmaries and to realize the smiles of children during the integration with the clowns. Reported that the visits, as well as diminishing the stress of children, caregivers and assist in the recovery of patients, also act in humane training of health professionals and contributes to the practice of multidisciplinarity. Conclusions: The respondents believe that Project Y can positivelyinfluence the training of health professionals, expanding interdisciplinary practice and providing complete pain relief of the patient. Thus, enhances communication of those who share the hospital environment and relieve human suffering.